Upaya Guru Majlis Ta’lim Dalam Mengatasi Kesulitan Membaca Al Qur’an Pada Orang Tua - Chasanah, Aminatul; Sukati (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine (1) the level of the ability to read the Koran to parents in Karanganom Sitimulyo Piyungan Hamlet, Yogyakarta. (2) The factors of difficulty in reading the Qur'an for parents in Karanganom Sitimulyo Piyungan, Bantul, Yogyakarta. (3) Efforts by Ta'lim Majlis teachers to overcome difficulties in reading the Qur'an to parents in Karanganom Sitimulyo Piyungan, Bantul, Yogyakarta. In this study the sample was 28 parents in Karanganom Sitimulyo Piyungan Bantul Yogyakarta which was determined using simple random sampling technique, namely the researchers took a random sampling of 25%. Data collection techniques use observation, interviews, documentation and tests. The results showed that the level of the Qur'anic reading ability of parents in Karanganom Sitimulyo Piyungan, Bantul, Yogyakarta varied. Parents who fall under the title are 29% or 8 people, the predicate is 64% or 18 people, the predicate is 7% or 2 people. The predicate is very good 0% or none. Factors difficulty in reading the Qur'an to parents in Karangnom Sitimulyo Hamlet, Piyungan Bantul, Yogyakarta because (1) Difficulty understanding Tajweed (2) Lack of family support (3) Declining interest (4) Rarely reading because of busy (5) Decreased function five senses (6) The lack of majelis ta'lim for parents. The efforts of the Ta'lim Majlis teacher to overcome the difficulties of reading the Koran to parents in Karanganom Sitimulyo Piyungan Bantul, Yogyakarta are: a) Approach to parents. b) Do individual guidance. c) Pack the materialinterestingly. d) Provide motivation. e) Drill Method